Control of SARS-CoV-2 infection after Spike DNA or Spike DNA+Protein co-immunization in rhesus macaques - Rosati, Margherita; Agarwal, Mahesh; Hu, Xintao; Devasundaram, Santhi; Stellas, Dimitris; Chowdhury, Bhabadeb; Bear, Jenifer; Burns, Robert; Donohue, Duncan; Pessaint, Laurent; Andersen, Hanne; Lewis, Mark G.; et al. (PLoS pathogens, 2021)
The speed of development, versatility and efficacy of mRNA-based vaccines have been amply demonstrated in the case of SARS-CoV-2. DNA vaccines represent an important alternative since they induce both humoral and cellular immune responses in animal models and in human trials. We tested the immunogenicity and protective efficacy of DNA-based vaccine regimens expressing different prefusion-stabilized Wuhan-Hu-1 SARS-CoV-2 Spike antigens upon intramuscular injection followed by electroporation in rhesus macaques. Different Spike DNA vaccine regimens induced antibodies that potently neutralized SARS-CoV-2 in vitro and elicited robust T cell responses. The antibodies recognized and potently neutralized a panel of different Spike variants including Alpha, Delta, Epsilon, Eta and A.23.1, but to a lesser extent Beta and Gamma. The DNA-only vaccine regimens were compared to a regimen that included co-immunization of Spike DNA and protein in the same anatomical site, the latter of which showed significant higher antibody responses. All vaccine regimens led to control of SARS-CoV-2 intranasal/intratracheal challenge and absence of virus dissemination to the lower respiratory tract. Vaccine-induced binding and neutralizing antibody titers and antibody-dependent cellular phagocytosis inversely correlated with transient virus levels in the nasal mucosa. Importantly, the Spike DNA+Protein co-immunization regimen induced the highest binding and neutralizing antibodies and showed the strongest control against SARS-CoV-2 challenge in rhesus macaques.